Improving Cognitive Skills In School-Age Children about Prevention of Diabetes Mellitus through Diabetamon Games - Andriyanto, Arief; Zainuri, Imam; Yuniarti, Enny Virda; Zakiyah, Ana (Jurnal Kesehatan Manarang, 2025)
Diabetes is not solely an adult health issue—it has also become a growing concern among school-age children. The rise in childhood obesity has contributed to an increasing incidence of type 2 diabetes in children and adolescents, which now parallels and sometimes surpasses that of type 1 diabetes. Parents need to take proactive steps to prevent this disease by providing accurate information to their children. Children can also gain knowledge through educational approaches aimed at enhancing their cognitive abilities, including through games. This study aims to analyze the effectiveness of the Diabetamon game in improving cognitive skills related to diabetes mellitus prevention among school-age children. This research used a quasi-experimental design with a control group. A total sample of 99 school-age children was divided into an intervention group (47 students) and a control group (52 students), selected using proportional random sampling. The study was conducted over a one-month period, with the intervention delivered twice a week for 60 minutes over three weeks. Data collection instruments included a questionnaire and an observation checklist to assess children’s snack habits. Statistical analysis was performed using paired t-tests to examine within-group changes and independent samples t-tests to compare between-group differences, with a significance level of p<0.05. The results showed that the cognitive abilities of the intervention group improved significantly compared to the control group. The Diabetamon game was proven effective in enhancing school-aged children's knowledge about the importance of consuming fruits and vegetables, in line with the pillars of balanced nutrition and physical activity.